Effect Economic Value Added and Market Value Added to Stock Return Sub-Sector Cement Industry on BEI 2019-2023 - Diana Riyana Harjayanti; Risma Marliana; Ifa Nurmasari; Dony Oktariswan (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
The purpose of this study is to determine the effect of Economic Value Added (EVA) and Market Value Added (MVA) on stock return in manufacturing companies sub-sector cement industry listed on the Indonesia Stock Exchange period of 2019 – 2023. This research was conducted using a quantitative analysis method. This study using panel data regression analysis calculate in Eviews 13 program. Results of study shows that partially Economic Value Added (EVA) on Stock Return with value t-value 1.188 with a positive direction of < ttable 2.048 and a significant value of 0.2475 > 0.05 which means that Economic Value Added does not have a significant effect on stock return especially in manufacturing companies-sub sector cement industry period 2019 - 2023. And partially Market Value Added (MVA) to the Return of Stocks with a calculated value of t-value -3.990 with a negative direction > ttable 2.048 and a significant value of 0.0006 < 0.05, This means that Market Value Added (MVA) has a significant effect on stock returns, especially in manufacturing companies-sub sector cement industry period the 2019 - 2023 period. And simultaneously (together) Economic Value Added (EVA) and Market Value Added (MVA) have a significant effect on Stock Return with a calculated value of F-value 6.1407 with a positive direction > Ftable 2.510 and 0.0004 < 0,05. And also the result of the determination coefficient value (Adjusted R Square) of 0.553 or 55.3% and the remaining 44.7% was influenced by other variables outside the research model.